Experimental Study of Vibration Effect on Porous Media (Journal of University of Babylon for Engineering Sciences, 2018)
The evolution of techniques required to mobilize reservoir fluids at critical saturation is important because of global needs for petroleum, and because of the necessity to conserve the subterranean water that deteriorated because of the slowness of the dismantling of persistent organic pollutants. The acoustic waves of low frequency are one of these methods, but until recently the absence of understanding of the vibration effect to displace oil prevent vibration application in the field. This paper proves that oil permeability increased when the vibration induced in porous media; that vibration makes resorting to the rock grains, which stimulate passage for liquid moving through the reservoir. The capillary pressure and reservoir pressure should be taken in consideration in order to make optimum validation for vibration stimulation.